The plea of provocation in criminal law / Khalijah Ahmad - Ahmad, Khalijah (Diploma in Law, 1986)
Provocation is a defence to a charge of murder at 1 Commonon Law, entitling the accused to be convicted of mans 1aughter . These Common Law defence of provocation owed its origin to the growth by the late sixteenth century of a consciousness that different modes of inflicting death reflected different shades of moral capability, and that each of the forms of killing these was prescribed an appropriate punishment. By the first half of the sixteenth century the practice had evolved whereby one who killed in necessary and reasonable self defence was permitted to go free. Devlin J., in what the Court of Criminal appeal described as a .classic direction' as follow: “Provocation is some act, or series of acts, done by the dead man to the accused, which would cause in any reasonable person, and actually causes the accused, a sudden and temporary loss of self-control rendering the accused so subject to passion as to make him or her for the moment not master of his mind”2.